PENYULUHAN DAN PEMERIKSAAN FAKTOR RISIKO UNTUK MENCEGAH KEJADIAN STROKE ISKEMIK - Pramaswari, A.A.A.A.; Tini, K.; Adnyana, I.M.O.; Susilawathi, N.M.; Wijayanti, I.A.S.; Putra, I.B.K.; Indrayani, I.A.S.; Pramana, N.A.K.; Mahadewi, N.P.A.P.; Laban, E.P.; Sutama, I.K.R. (Buletin Udayana Mengabdi; Vol 24 No 2 (2025): Buletin Udayana MengabdiDO - 10.24843/BUM.2025.v24.i02.p07, 2024)
Ischemic stroke is a neurologic problem that can caused permanent disabilities and affect daily activities. Considering the high risk of permanent disability and even mortality, reducing the incidence of stroke is an important approach. This community service purpose to reduce the incidence of stroke by increasing public knowledge and awareness to prevent strokes. This activity was held in Ayunan village, Abiansemal subdistrict, Badung regency in August 18th 2023 with 62 participants. This act consists of health education regarding prevention of ischemic stroke, followed by examination of stroke risk factors, and ends with a consultation session with neurologist.Participant enthusiasm is very high and examination of risk factors for ischemic stroke has been carried out and can be a motivation for the participant to prevent strokes. Keywords: Ischaemic Stroke, Primary Prevention, Risk Factor, Secondary Prevention